Impacted mandibular third molar: Comparison of coronectomy with odontectomy - Kanika Singh; Sanjeev Kumar; Sukumar Singh; Vijay Mishra; Pradeep Kumar Sharma; Deepak Singh (Wolters Kluwer Medknow Publications, 2018)
Aim: Damage to the inferior alveolar nerve (IAN) while extracting lower third molars is often caused by the intimate relationship between the nerve and the roots of the teeth. The aim of this study was to compare the sequelae of coronectomy with odontectomy in impacted mandibular third molars. Patients and Methods: This study included thirty patients which were divided into two groups, Group-I (test group) including 15 patients undergoing coronectomy and Group-2 (control group) of 15 patients undergoing odontectomy. Investigations included digital orthopantomogram. The parameters for this study included pain, swelling, nerve paresthesia, trismus, postoperative infection, postoperative wound dehiscence, postoperative pocket depth, and migration. Results: In Group-1 (coronectomy group), the patients underwent follow-up for 6 months to evaluate migration of the retained mandibular third molar root which was in proximity with the IAN. There was a mean increase in migration when the distance from the inferior border of IAN until the apex of the retained mandibular third molar root was measured which was by 3.43 mm after 6 months of follow up. Conclusion: On statistical analysis, the result in this study showed no statistical difference in both the groups in all the parameters that were taken.